Cervical dystonia: Injecting botulinum neurotoxin into semispinalis capitis improves goose-neck posture - Tai Ngoc Tran; Minh Le; Thuong Huyen Thi Dang; Daniel Truong (Clinical Parkinsonism & Related Disorders, 2019)
We describe a patient with goose-neck posture as the presenting form of cervical dystonia. In our case, the bilateral semispinalis capitis muscles were hypertrophic, thick, and overactive while both splenius capitis and sternocleidomastoid muscles were normal. In this single case experience, we demonstrated that the semispinalis capitis muscle may play a primary role in causing a goose-neck posture and the observed forward sagittal shift may be a compensatory or overflow activity of neck flexor muscles. Therefore, botulinum toxin injection to the semispinalis capitis muscles can be considered in the management of patients with goose-neck posture.